Comparative effectiveness of exercise training program in patients with heart failure: protocol for a systematic review of randomised controlled trials and network meta-analysis - Min Gao; Yangxi Huang; Qianyi Wang; Zejuan Gu; Guozhen Sun (BMJ Open)
Introduction Heart failure (HF) is an end-stage of numerous heart diseases including hypertension, coronary heart disease and arrhythmia, in which the heart is unable to perform its circulatory function with sufficient efficiency due to structural or functional dysfunction (systolic or diastolic alterations). Strategies such as exercise rehabilitation may improve cardiac function, exercise capacity and health-related quality of life and reduce anxiety and depression in patients with HF. However, the relative effectiveness as well as the hierarchy of exercise interventions have not been well established, although various exercise options are available. Therefore, this protocol proposes to conduct a network meta-analysis (NMA) aiming to compare the effectiveness of different types of exercise training in patients with HF.Methods and analysis PubMed, Embase and the Cochrane Library will be searched from inception to March 2021 for relevant randomised controlled trials. Other resources, such as Google Scholar and Clinical Trials.gov will also be considered. Studies assessing exercise rehabilitation in patients with HF will be selected. Two independent reviewers will identify eligible trials. The PEDro risk of bias assessment tool will be used to assess the quality of the included studies. Bayesian NMA will be used when possible to determine the comparative effectiveness of the different exercise interventions. The mean ranks and surface will estimate the ranking probabilities for the optimal intervention of various treatments under the cumulative ranking curve. Subgroup, sensitivity and meta-regression will be conducted to explain the included studies’ heterogeneity if possible. We will also use the Grading of Recommendations, Assessment, Development, and Evaluation system to assess the strength of evidence.Ethics and dissemination This systematic review and NMA will synthesise evidence on the effectiveness of the different exercises in patients with HF. The results will be submitted to a peer-reviewed journal. No ethical approval will be required because the data used for the review will be exclusively extracted from published studies.PROSPERO registration number CRD42020165870.